Hepatoprotective Effects of Ginseng in Rats Fed Cholesterol Rich Diet - Uluısık, Deniz; Keskin, Ercan (Acta Scientiae Veterinariae, 2016)
Background: Ginseng species having been used in various traditional herbal therapies for many years in worldwide. In recent years, hyperlipidemia, hypercholesterolemia and obesity have become serious health problems. These are considered risk factor for metabolic and organic diseases such as atherosclerosis, fatty liver, diabetes. Therefore, prevention and treatment of these disorders are significant for ensuring comfortable and healthy life. It has been also stated that ginseng saponin suppressed liver enzyme increments caused by feeding with high cholesterol or fatty diet. The present study was undertaken to evaluate the effect of ginseng on liver enzymes of rats fed cholesterol-rich diet. Materials, Methods & Results: In this study, 24 healthy adult male Wistar Albino rats were equally divided into three groups as control group (K), cholesterol group (C), and cholesterol + ginseng group (CG). The K group had ad libitum access to a standard rat diet for 40 days. The C and CG groups had ad libitum access to the same diet containing 5% cholesterol powder and 5% cholesterol + 1 g/kg Panax ginseng root powder, respectively, for 40 days. On the 40 th day of the study, blood samples were taken from 8 animals in each group. At the end of the study, plasma samples were analyzed for aspartase transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and gamma-glutamyltransferase (GGT) levels. The data were analyzed using one-way ANOVA. Differences among the groups were determined by Duncan’s multiple range test. In this study, the results showed that AST, ALT, GGT levels in cholesterol group significantly increased compared to control group but these parameters in cholesterol + ginseng group significantly decreased with ginseng administration compared to cholesterol group (P < 0.05). There was no significant difference among the groups with regard to ALP level. Discussion: AST, ALT, GGT and ALP are considered to be the markers of organ disfunction, indicator of cellular damage, cell leakage and the loss of cell membrane integritiy in the liver, kidney, heart and other organs. It was investigated effect of ginseng on some hepatic enzymes in rats fed a high cholesterol diet. In this study, feeding with the diet for 40 days resulted in elevation AST, ALT, GGT compared control levels (P < 0.05). In some studies, using high cholesterol diet caused hepatic injury in animal and human models. The harmful effects of high cholesterol on liver have been attributed to hepatic fibrosis, lipid peroxidation, increased endogenous oxidative stress, inducing cellular damage and engendering hyperlipidemia. Increases in ALT, AST, GGT levels are thought to be due to oxidative stress related to hyperlipidemia in present study. In this study, treated with red Korean ginseng extract significantly prevented the elevations in AST, ALT, GGT levels (P < 0.05). The use of ginseng as an unconventional health treatment is gaining remarkable popularity among the people. It has been known that ginseng have assorted beneficial pharmacological effects and hypolipidemic, antidiabetic, antioxidative and immunostimulator effects have been stated among its pharmacological properties. These beneficial effects of ginseng on liver enzymes attributed to its active components known as ginsenosides. In the light of the findings, Panax ginseng root powder may be useful for hepatic damage and fibrosis associated with high cholesterol diet.